NITRITE AND NITRATE CONTENT OF FOOD COMPOSITION OF NORTHERN VILLAGES OF IRAN - M.Rahmanian; M.Azar; SH.Khalili (Tehran University of Medical Sciences, 1982)
In epidemiological study of esophageal carcinoma which was conducted in Nov.1966 in Iran, the incidence cases in the east area of Mazandaran (Hottan-Gharagol) specifically in the Torkaman Region was noticeable. The frequency of the disease was gradually declined from east to west for instance in Gillan (Pamsar-kyasara) the incidence was low. Since 1968 a Joint-Iran (Institute of Nutrition Sciences and Food Technology and Public Health University) and IARC (International Agency for Research on cancer) started and survey in the Target area of Norghern villages. One of the factors which were covered under this survey was the determination of environmental carcinogenic agents such as nitrite and nitrate which is precursor of Nitrosamine. Nitrite was determined by colorimetric standard method, and on a cadmium column. In this project 200 samples from different groups of food were determined and the result was reported as mg percent of nitrite and nitrate.